Plant Growth Analysis of Jack Been (Canavalia ensiformis L.) at Different Spacing to Determine the Application Time of Cutback Technology - N. Nurmuliana; Muh. Akhsan Akib (Universitas Sembilanbelas November Kolaka, 2019)
AbstractThe growth of jack bean (Canavalia ensiformis L) is affected by genetic and environmental factors. One of the environmental factors involved is growing space. Growing space related to each plant of areas occupied is stated by the distance between plants. A Research has been conducted as long three months in dry season with average daily temperature of 25 to 31OC on altitude of 25 to 500 meter, to determine the timing of the application of cutback technology based on an analysis of growth of jack bean plants (Canavalia ensiformis L) in different growth spaces. The research was conducted in the trial form using a randomized block design. Variables of plants growth analysis observed is leaf area index (LAI), leaf area is computed by gravimetric method; net assimilation rate (NAR), and relative growth rate (RGR) is determined based on the dry weight of plants; in all three rooms grew, namely 75 cm x 100 cm (control), 75 cm × 75 cm and 75 cm × 50 cm, each repeated three times. The result shows that the trend of leaf area index increased at net assimilation rate (g-1.cm-2.week-1) and relative growth rate (g-1.g-1.minggu-1) decreasing at the time the plant to the age 8 weeks after planting. The best time for the application of reduction technology to jack bean plants (Canavalia ensiformis L) in all tested growing spaces, is recommended when plants are between 7 and 8 weeks after planting